2018
DOI: 10.1109/tsp.2018.2866844
|View full text |Cite
|
Sign up to set email alerts
|

Performance Limits With Additive Error Metrics in Noisy Multimeasurement Vector Problems

Abstract: Real-world applications such as magnetic resonance imaging with multiple coils, multi-user communication, and diffuse optical tomography often assume a linear model where several sparse signals sharing common sparse supports are acquired by several measurement matrices and then contaminated by noise. Multi-measurement vector (MMV) problems consider the estimation or reconstruction of such signals. In different applications, the estimation error that we want to minimize could be the mean squared error or other … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…We call the function (7) as free entropy function 4 . According to [12], [13], optimizing E that maximizes the free entropy function (7) corresponds to the minimum MSE (MMSE) of specific choices of system parameters, i.e., ρ, α, C g , ∀g, in the Bayes-optimal condition. Setting the first order derivative of Φ(E) with respect to the matrix E into zero, we get the following equation.…”
Section: A Free Entropy Function Derivation Via Replica Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We call the function (7) as free entropy function 4 . According to [12], [13], optimizing E that maximizes the free entropy function (7) corresponds to the minimum MSE (MMSE) of specific choices of system parameters, i.e., ρ, α, C g , ∀g, in the Bayes-optimal condition. Setting the first order derivative of Φ(E) with respect to the matrix E into zero, we get the following equation.…”
Section: A Free Entropy Function Derivation Via Replica Methodsmentioning
confidence: 99%
“…In the statistical physics literature, the free entropy of a system reflects the macro performance that characterizes some thermodynamic properties of the system [15]. Some related works in the signal processing literature have also shown that evaluating the fixed point of free entropy function provides the minimum MSE (MMSE) prediction for signal recovery and the achievable MSE for the AMP framework [12], [13]. For the massive connectivity scenario, evaluating the free entropy function of our system (1) provides an analytic tool to measure the performances metrics of joint AUD and CE.…”
Section: Replica Analysis On Joint Aud and Cementioning
confidence: 99%
See 1 more Smart Citation
“…In words, the ROC captures trade-offs between false positives and negatives, and increasing the AUC reflects better estimation. While standard GAMP minimizes the MSE [7], other error metrics can be minimized [10], [11].…”
Section: A Gamp Illustrationmentioning
confidence: 99%
“…In words, the ROC captures trade-offs between false positives and negatives, and increasing the AUC reflects better estimation. While standard GAMP minimizes the MSE [7], other error metrics can be minimized [10], [11]. The top pannel of Fig.…”
Section: A Gamp Illustrationmentioning
confidence: 99%